Torsion of wandering spleen involving the pancreatic tail. (February 2020) - Colombo, Francesco; D'Amore, Pierluigi; Crespi, Michele; Sampietro, Gianluca; Foschi, Diego
Abstract: Background: Wandering spleen (WS) is a rare clinical entity resulting from the absence or maldevelopment of the ligaments normally involved in the attachment of the spleen in its normal position. WS can be a cause of acute abdomen leading to different complications ranging from torsion of the vascular pedicle to spleen infarction. Often, in absence of symptoms, it is an occasional finding during radiological exams and surgery represents the gold standard in the management of this unusual condition. Case presentation: We present a case of wandering spleen in a young nulliparous female with an history of recurrent abdominal pain. A preoperative CT-scan of the abdomen showed the presence of a multi-infarcted spleen twisted several times around its vascular pedicle, involving the tail of pancreas. The patient was electively treated with laparoscopic splenectomy. Conclusions: A laparoscopic approach is feasible in the treatment of this pathology. A correct and timely diagnosis of this condition is crucial to allow an organ preserving surgery. There are only few reported cases in literature describing an involvement of the tail of the pancreas in the torsion of the vascular pedicle. Complete excision of the ectasic veins tributaries of the splenic vein avoids the risk of postoperative vein thrombosis and bleeding. Highlights: Wandering spleen is a rare clinical entity resulting from the absence or maldevelopment of the ligaments normally involved in the attachment of the spleen. CT-scan showed a multi-infarcted spleen twisted several times around its vascular pedicle, involving the tail of pancreas. Laparoscopic splenopexy or splenectomy are the gold standard for the treatment of wandering spleen.